Evaluasi Sikap Dan Perilaku Siswa Terhadap Lingkungan Hidup Dan Pembangunan Berwawasan Lingkungan Di Madrasah - Wahyuningtiyas, Neni (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Environmental education is one effort to realize environmental sustainability for present until future. Explicitly, it shows that human effort to saveenvironmental must be done continuously, relay from one generation to the next generation. In fact, there is problem about behavior and attitude of student class XI at MA Nurul Ulum Munjungan Trenggalek towards environmental sustainability. Most of student have less concern towardsenvironmental sustainability, for examples throwing the rubbish everywhere, letting classroom dirty, plant that are not caring well, and excessive use of water. In order to describe the behavior and attitude of students towardsenvironmental and development based on environmental, evaluation about behavior and attitude of student is needed to be done actually and systematically.Keywords: Evaluation, behavior, environmental behavior